2017
DOI: 10.1167/iovs.16-21115
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Microcirculation After Intravitreal Ranibizumab Injection in Eyes With Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: An IVR injection leads to a transient vasoconstriction of the retinal arteries and veins and a reduction of the retinal blood flow and velocity in both the occluded and nonoccluded quadrants. The changes in retinal microcirculation might be related to the improvement of the macular edema and vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 54 publications
4
30
0
Order By: Relevance
“…While some reports demonstrate adverse vasoconstrictive effects on retinal perfusion that include a reduction in retinal vessel diameters and flow velocities, [31][32][33][34] there are others that demonstrate positive effects of anti-VEGF therapy on retinal perfusion, such as prevention of retinal nonperfusion. 35,36 In the current study, quantitative OCTA imaging identified that both VD and FAZ within the 3 3 3-mm area did not differ significantly during the course of anti-VEGF therapy for 12 months in patients with RVO.…”
Section: Discussionmentioning
confidence: 99%
“…While some reports demonstrate adverse vasoconstrictive effects on retinal perfusion that include a reduction in retinal vessel diameters and flow velocities, [31][32][33][34] there are others that demonstrate positive effects of anti-VEGF therapy on retinal perfusion, such as prevention of retinal nonperfusion. 35,36 In the current study, quantitative OCTA imaging identified that both VD and FAZ within the 3 3 3-mm area did not differ significantly during the course of anti-VEGF therapy for 12 months in patients with RVO.…”
Section: Discussionmentioning
confidence: 99%
“…Fukami et al [12] studied the effects of IVR injection in eyes affected by ME in branch RVO and found that IVR injection leads to a transient vasoconstriction of the retinal arteries and veins and a reduction of the retinal blood flow and velocity in both occluded and not occluded quadrants.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, LSFG (Softcare, Fukutsu, Japan) is a fundus camera equipped with a diode laser (wavelength, 830 nm) and a charge-coupled device sensor (750 × 360 pixels), which are used to obtain images of the pattern of speckle contrast produced by interference as laser light is scattered by red blood cells moving through vessels in the ocular fundus. Light reflected from the tissue produces a speckled pattern on the plane where the area sensor is focused and reflected light from moving erythrocytes causes blurring of the speckle pattern [12]. e same site can be measured by using the autotracking system.…”
Section: Laser Speckle Flowgraphy Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…During anti-VEGF treatment, RNFL edema remitts with the resolution of BRVO. Moreover, anti-VEGF treatment significantly reduces peripapillary blood flow volume and vessel diameter (17). These changes bring pRNFL thickness to "normal" levels in general.…”
mentioning
confidence: 93%